SAT0504 Prevalence and Correlates of Household Work Related Musculoskeletal Disorders in Low Back Region among Sri Lankan Housewives. (15th July 2016) - Ranasinghe, P.D.; Atukorala, I.; Samaranayake, A.; Gunawardana, N.S.
Abstract : Background: Household work is a significant cause of low back disorders particularly in the South Asian settings where work is manually performed and labour intensive. However, the prevalence household work related back pain in south Asian settings is unknown. Objectives: To determine the prevalence of household work related musculoskeletal disorders (HWMSD) in low back region and its correlates among 20–50 year old housewives in an urban setting in Sri Lanka Methods: A community based cross-sectional study was conducted on a sample of eligible housewives (n=1102) in an urban Sri Lankan setting using the multi-stage cluster sampling technique. Participants were women whose sole occupation was unpaid household work in their own homes for a minimum of 4 hours (continuously or intermittently) daily for at least 5 days a week, for a minimum of 2 years. Those with menopause, inflammatory arthritis, pregnant or in postpartum period, previous disability unrelated to household work were excluded. A novel validated tool- household work related musculoskeletal disorder questionnaire (HWMQ) with a sensitivity of 94.5% (91.7–97.3) and specificity of 99.3% (98.3–100) was used to identify HWMSD in low back. Correlates of HWMSD in low back region were conceptualized as physical exposures related to the housework, psychosocial factors and individual level factors. An analytical cross-sectional study using multivariate analyses comparing those with HWMSD of the low back region (n=397) and without HWMSD in any region of the body (n=405) determined the correlates of HWMSD in the low back region among housewives. Results: The majority of housewives were performing multiple of household chores [cooking related activities (n=1031, 93.6%), hand washing clothes (n=811, 73.6%), ironing (n=972, 88.2%), sweeping indoor and outdoor (n=374, 33.9%), cleaning bathrooms/toilets (n=912, 82.8%), shopping (n=725, 65.8%) and carrying children (n=374, 33.9%)]. The prevalence of HWMSD in low back region among 20–50 year old housewives was 36% (95%CI: 33.1%>39%). Correlates of HWMSD in low back region among 20–50 year old housewives identified as significant are shown in Table 1 . Conclusions: Prevalence of HWMSD in low back was high among housewives in Sri Lanka. The study identified several modifiable and a few non-modifiable physical exposures, psychosocial factors and individual level factors as significant correlates of HWMSD in low back region. Acknowledgement: Medical Research Institute, Sri Lanka Disclosure of Interest: None declared